The m6A regulators in prostate cancer: molecular basis and clinical perspective - Cao, Yu; Jia, Man; Duan, Chunyan; Yang, Zhihui; Cheng, Bo; Wang, Ronghao (Frontiers in Pharmacology, 2024)
Prostate cancer (PCa) is the second leading cause of cancer-related death among men in western countries. Evidence has indicated the significant role of the androgen receptor (AR) as the main driving factor in controlling the development of PCa, making androgen receptor inhibition (ARI) therapy a pivotal management approach. In addition, AR independent signaling pathways also contribute to PCa progression. One such signaling pathway that has garnered our attention is N6-Methyladenosine (m 6 A) signaling, which refers to an chemical modification on RNA with crucial roles in RNA metabolism and disease progression, including PCa.